Objectively measured access to recreational destinations and leisure-time physical activity: Associations and demographic moderators in a six-country study. (September 2019) - Gidlow, Christopher; Cerin, Ester; Sugiyama, Takemi; Adams, Marc A.; Mitas, Josef; Akram, Muhammad; Reis, Rodrigo S.; Davey, Rachel; Troelsen, Jens; Schofield, Grant; Sallis, James F.
Abstract: Within the growing body of research linking neighbourhood environmental attributes with physical activity, associations between recreational destinations and non-walking leisure-time physical activity (LTPA) are rarely studied, and to date, not across multiple cities. We examined six potential associations of objectively-measured access to private recreational facilities (e.g., fitness centres, swimming pools) and parks with adults' non-walking LTPA (e.g., swimming, cycling, tennis), using data gathered with consistent methods from adults living in international cities with a range of environment attributes. The potential effects of socio-demographic moderators and between-city variations were also examined. Data from 6725 adults from 10 cities (6 countries) were gathered. Adults were more likely to engage in non-walking LTPA if they had a greater number of private recreational facilities within 0.5 or 1 km of the home, particularly in women, and if they lived closer to a park. The amount of non-zero LTPA was only associated (positively) with the number of recreational facilities within 1 km. Relationships between amount of LTPA and park proximity appear complex, with likely contextual and cultural differences. Improving access to private recreational facilities could promote non-walking LTPA, especially in women. Highlights: We analysed data from adult residents of 10 environmentally diverse cities. Likelihood of non-walking LTPA was associated with recreational facility and park access. Private recreational facilities were more important for women's non-walking LTPA. Associations of park proximity with non-walking LTPA vary by city and social group.